2008
DOI: 10.1093/sleep/31.4.549
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Thermal Drive on Central Sleep Apnea in the Preterm Neonate

Abstract: 549 IN NEONATES, THE INCIDENCE OF APNEA DEPENDS ON A VARIETY OF FACTORS, SUCH AS BIRTH WEIGHT, 1 SEX, 2 GESTATIONAL AGE, 3 AND POSTNATAL AGE. 3,4 Central apnea is generally reported as occurring more frequently during active sleep than during quiet sleep. 2,3,[5][6][7] Many authors have pointed out that apnea incidence is also closely related to ambient temperature in both full-term [8][9][10] and preterm neonates 9,11,12 and that the rate of apneic events is increased by warm exposure (i.e., thermal drive).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2010
2010
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 44 publications
0
28
0
2
Order By: Relevance
“…Temperature values on the lower limits of the range seem to be associated with lower apnea rates, 47 so overheating should be avoided, even if more studies are needed to confirm this observation. …”
Section: Environmental Temperaturementioning
confidence: 95%
“…Temperature values on the lower limits of the range seem to be associated with lower apnea rates, 47 so overheating should be avoided, even if more studies are needed to confirm this observation. …”
Section: Environmental Temperaturementioning
confidence: 95%
“…In a recent study, less apnea was found at an incubator temperature of 30.4°C than at 32.5°C [91]. Of course, a number of factors play a role in incubator and baby temperature, but overheating may be a factor in AOP.…”
Section: Interventions For Premature Infants With Apneamentioning
confidence: 99%
“…Sleep apnoeas were scored only if they lasted 3 s or more, the duration usually used at this age (Gould et al. , 1977; Tourneux et al. , 2008).…”
Section: Methodsmentioning
confidence: 99%